FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS STUNTING ANAK USIA 24-59 BULAN DI WILAYAH KERJA UPK PUSKESMAS SIANTAN HULU - Mentari, Suharmianti; Hermansyah, Agus (Pontianak Nutrition Journal, 2018)
Stunting incidence in infants is one of the nutritional problems globally. Stunting is related to infection, diet, mother’s education level, mother’s work status, birth length. The design of this study was Cross Sectional and Retrospective Cohort with Chi-square test. The research was conducted in the Siantan Hulu Health Center UPK Working Area in June to July 2016. The results of the univariate analysis showed that stunting status of children with no stunting category was 68.5%, infection with no infection category was 59.6%, diet with categories both at 74.2% and the birth length of children with normal categories of 68.5%. After analyzed using the chi square test showed there was a relationship between infection (p = 0.004), diet (p = 0.006) and child birth length (p = 0,000) on stunting status of children aged 24-59 months in the Siantan Hulu Health Center UPK Working Area.